Down-regulation of oxidative stress and COX-2 and iNOS expressions by dimethyl lithospermate in aged rat kidney - Choi, Yeon Ja; Kim, Hyung Suk; Lee, Juyoun; Chung, Jin; Lee, Jun Sik; Choi, Jae Sue; Yoon, Taek Rim; Kim, Hyung Keun; Chung, Hae Young (Archives of pharmacal research, 2014)
Oxidative stress has been proposed to be a major cause of aging and many age-related diseases. Peroxynitrite (ONOO − ), formed from the reaction of superoxide ( • O 2 − ) and nitric oxide (NO), is a cytotoxic species that can oxidize various cellular components, such as proteins, lipids, and DNA. The present study investigated whether dimethyl lithospermate (DML), isolated from Salvia miltiorrhiza , modulates age-related increases of ONOO − , NO, and reactive species (RS) levels and expressions of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS). For this study, 20-month-old rats were intraperitoneally injected with 5 or 10 mg/kg/day of DML, and 6-month-old rats were used as young control animals. Our results indicated that DML reduces ONOO − levels in a dose-dependent manner. The data also revealed that DML has significant inhibitory effects on NO metabolites and RS generation in a dose-dependent manner during aging. Furthermore, the results of Western blot analysis revealed that DML treatment reduces age-associated increases in COX-2 and iNOS expressions. Thus, this study found that DML caused the decrease of renal oxidative stress and COX-2 and iNOS expressions in aged rats. The significance of the present study is the finding of DML in its potential application against the aging process.